Nutrients and anti-nutrients of high chlorophyll - mungbean sprouts as affected by different periods of germination and sprouting stages - Vayupharp, Benjaruk; laksanalamai, varaporn (International Journal of Agricultural and Biological Engineering, 2013)
Abstract: The variation of nutrient and anti-nutrient compounds in commercial mungbean cultivars (Chinat 72, MS-1, Chinat 80, and L3-8) during seven periods of germination and sprouting was determined. The seeds were selected randomly at 6 h of soaking (1st stage), 23 h (2nd stage), 47 h (3rd stage), 71 h (4th stage), 77 h (5th stage) of sprouting, and 12 h, and 24 h of sunshine exposing (6th and 7th stage, respectively). It was found that nutrition compositions (including protein content, crude fiber content, vitamin C content, total minerals, and HCL-extractability of minerals) of all cultivars significantly increased with germination and sprouting. At the last stage, the total phenol was the highest amount which was not significantly different from all cultivars. The total antiradical capacity (%, DPPH inhibition) increased up to the maximum value in the last two stages of sprouting. The results showed that the phytic acid, the anti-nutrient component decreased with the consequence of germination, and reached the untraceable value at the last stage. In addition, the highest amount of chlorophyll (7.15- 8.99 mg/100 g) was found in Chinat 72 and MS-1 cultivars at the last stage of sprouting, comparing to Chinat 80 and L3-8 cultivars. It is therefore recommended to consume high chlorophyll mungbean sprout with the benefits of high nutrient constituents and low price purchase comparing to other green vegetables.Keywords: high chlorophyll, phytic acid, total phenolic content, radical scavenging activity, HCl extractability of minerals, mungbean sproutsDOI: 10.3965/j.ijabe.20130604.014Citation: Vayupharp B, Laksanalamai V. Nutrients and anti-nutrients of high chlorophyll